Interactive Image Segmentation for Cochlea Implant Planning based on DVT Data - Killguß, Nathalie; Wittenberg, Thomas; Franz, Daniela; Eixelberger, Thomas; Rupp, Robin; Hofer, Mathias (Current Directions in Biomedical Engineering, 2019)
Cochlea Implant (CI) planning is usually based on preoperative obtained CT or MRI data, visualising risk structures in the petrosal bone. In the past years, Digital Volume Tomography (DVT) with an increased spatial resolution and reduced radiation has become more important in the clinical routine for otology. In this work we propose an extension of our interactive "wizard"-guided approach for the interactive segmentation of the middle and inner ear structures for the use with DVT data. Different filter pipelines enable the user to interactive segment the acoustic canal, ossicles, tympanic cavity, facial nerve, chorda tympani, round window, cochlea and semicircular canals. The approach has been evaluated on six pre-operative acquired DVT datasets by an ENT expert. Results imply that the proposed method can handle DVT well and can potentially be used for interactive OR planning.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Cochlea Implant planning; Digital Volume Tomography; Image processing; Interactive Segmentation